Metathesis reactions with a low-cost spinning disk system. Issue 4 (2nd October 2019) - Kazi, Shahid A.; Clark, Peter; Campi, Eva. M.; Jackson, W. Roy; Hearn, Milton T. W.
ABSTRACT: Experimental procedures have been developed to provide at the laboratory scale an efficient and relatively inexpensive continuous flow processing system to undertake metathesis chemistry. Glass discs, coated with porous silica particles impregnated with Grubbs (I) generation or Hoveyda–Grubbs (II) generation catalysts through non-covalent interactions, have been successfully used as annular zones for in situ metathesis reactions. The supported catalysts were active for ring closing metathesis and self-metathesis reactions with a variety of substrates with nearly quantitative conversion depending on the substrate structure. Advantages of these procedures include the ability to conduct reactions efficiently at small (low mmole) scale under ambient laboratory conditions, thereby avoiding the need for high energy/thermal procedures. Multiple experiments can be undertaken during the same day if catalyst screening is required. Moreover, separation of starting materials from products can be achieved using the same unit operations, avoiding the need for additional purification steps, thereby reducing the total solvent consumption. GRAPHICAL ABSTRACT: